Preparation method of urchin-shaped SiC reinforced composite aerogel thermal insulation material
Patent Information
- Application Number
- CN202611486046.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]其二,外加组分自身极易团聚,难以在基体中均匀分散,从而无法发挥理想的增强效果
(1)界面结合强度显著提升:在硅源水解形成SiO2的过程中,一方面,海胆状SiC微粒的三维放射状结构与SiO2网络形成机械互锁,另一方面,碱处理引入的表面Si-O-活性位点与硅酸低聚物的Si-OH发生脱水缩合反应,形成牢固的化学键合界面,物理化学双重作用使界面结合强度较传统机械混合方式显著提高,可有效防止复合气凝胶的分层与开裂。
Smart Images

Figure CN122977816A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aerogels and thermal insulation materials, and more particularly to a method for preparing a sea urchin-shaped SiC-reinforced composite aerogel thermal insulation material. Background Technology
[0002] Silica (SiO2) aerogel, as a three-dimensional porous material with gas as the dispersed phase and solid particles as the dispersion medium, is valued for its low density (0.003-0.350 g·cm³). -3 High specific surface area (600-1000m²) 2 ·g -1 With its unique structure, including high porosity (80-99.8%) and nanopore size (1-100nm), it exhibits excellent thermal insulation performance and is considered one of the super thermal insulation materials with the lowest thermal conductivity. It has broad application prospects in fields such as batteries and aerospace thermal protection.
[0003] However, SiO2 aerogels experience severe skeletal collapse and sintering at temperatures above 650-800℃, leading to a sharp decline in thermal insulation performance and failing to meet long-term usage requirements at higher temperatures. To address this issue, researchers both domestically and internationally have conducted extensive modification work, primarily including the introduction of second components such as TiO2 and Al2O3 or the use of fiber reinforcement. However, existing methods still have the following significant limitations: Firstly, most modification strategies focus on a temperature range of around 800℃. For high-temperature environments of 800℃ and above, the long-term structural stability of SiO2 aerogel has not yet been fundamentally resolved.
[0004] Secondly, the added components are prone to agglomeration and are difficult to disperse evenly in the matrix, thus failing to achieve the desired enhancement effect.
[0005] Third, existing methods for preparing composite aerogels are difficult to precisely control the bonding process between the reinforcing phase and the SiO2 matrix. The process is complex and often involves multiple steps, making it difficult to achieve efficient and controllable integrated molding. Summary of the Invention
[0006] To address the aforementioned shortcomings, this invention provides a method for preparing a sea urchin-shaped SiC-reinforced composite aerogel insulation material. This invention uses Si powder and C powder as raw materials to catalytically grow sea urchin-shaped SiC nanostructures in situ on the surface of SiC microparticles. Through synergistic control of process parameters, the size and morphology of the nanostructures on the surface of the sea urchin-shaped SiC microparticles are precisely controlled. The modified sea urchin-shaped SiC microparticles are then polymerized in situ with a SiO2 aerogel precursor, achieving efficient, one-step in-situ preparation of the sea urchin-shaped SiC-reinforced composite aerogel insulation material. In the composite aerogel, the sea urchin-shaped SiC microparticles can more effectively penetrate and anchor within the SiO2 gel network, forming strong mechanical interlocking and interfacial bonding. Furthermore, the Si-OH introduced by alkali treatment chemically bonds with the silicon source. This dual physicochemical action significantly improves the interfacial bonding strength compared to traditional mechanical mixing methods, effectively preventing delamination and cracking of the composite aerogel. Furthermore, the urchin-like SiC microparticles can be oxidized to generate dense SiO2 in a high-temperature, oxygen-containing environment, which can in-situ fill microcracks and structural damage in the aerogel skeleton, effectively delaying the sintering collapse of the skeleton. In summary, this invention significantly improves the structural stability and thermal insulation durability of SiO2 aerogels under high-temperature environments through the synergistic effect of reinforcing phase introduction and high-temperature oxidation in-situ repair.
[0007] The specific technical solution of this invention is as follows: a method for preparing a sea urchin-shaped SiC-reinforced composite aerogel thermal insulation material, comprising the following steps: 1) Preparation of sea urchin-shaped SiC microparticles: Si powder and C powder are mixed and spread evenly on the bottom of the sintering container. Then, porous material pre-impregnated with phenolic resin and SiC microparticles loaded with catalyst are sequentially laid. The mixture is heated and vacuum sintered. The porous material is washed and peeled off with water to obtain SiC microparticles with SiC whiskers growing on the surface, i.e., sea urchin-shaped SiC microparticles.
[0008] The formation of urchin-like SiC particles in the above steps is based on a gas-liquid-solid (VLS) growth mechanism. First, a catalyst (such as Ni, Fe, etc.) is loaded onto the surface of the SiC particles, forming nanoscale alloy catalytic sites on the surface of the SiC particles. During the high-temperature reaction stage, the gaseous precursors SiO and CO are generated synergistically through multiple reactions: (i) H2O and CO2 released by the thermal decomposition of phenolic resin react with Si at high temperature to generate SiO, CO, etc.; the reactions are as follows: Si(s) + 2H2O(g) → SiO2(s) + 2H2(g); Si(s) + H2O(g) → SiO(g) + H2(g); Si(s) + CO2(g) → SiO(g) + CO(g); CO2(g) + C(s) → 2CO(g). (ii) The naturally occurring primary oxide layer on the surface of Si powder or the silicon dioxide generated by Si and trace oxygen in the system also undergoes a carbothermic reduction reaction with the carbon source at temperatures above >1400℃, further replenishing the gaseous precursors. The reactions are as follows: SiO2(s) + C(s) → SiO(g) + CO(g); SiO2(s) + Si(s) → 2SiO(g); SiO2(s) + CO(g) → SiO(g) + CO2(g). These gaseous precursors diffuse to the surface of SiC particles through the microchannels of the porous material, are absorbed by the catalyst droplets, and form a eutectic alloy liquid phase. When the concentration of Si and C in the droplets reaches supersaturation, SiC nuclei precipitate at the interface between the droplets and SiC particles and continue to grow one-dimensionally along a specific crystal orientation, eventually forming a urchin-like structure in which a large number of SiC nanowires radiate outward from the central SiC particle.
[0009] The functions of the porous material in this invention are: (i) to provide physical isolation. Without the porous material, SiC particles will react and sinter with Si and C powders at high temperatures, resulting in the particles directly agglomerating into large clusters. This would not provide an independent nucleation substrate for nanowire growth, nor would it yield a dispersed nanowire structure. (ii) to provide gas-phase transport channels. The microchannels in the porous material allow gas-phase precursors such as SiO and CO to pass through and diffuse uniformly to the surface of the isolated SiC particles, ensuring that the catalyst sites on the particle surface receive sufficient gas-phase raw material for nucleation and growth. (iii) The phenolic resin impregnated in the porous material is carbonized at high temperatures to transform into amorphous carbon, which is uniformly deposited on the inner wall of the pores. It continuously reacts with SiO to generate CO, significantly increasing the local carbon source supply concentration and the reducing power of the reaction atmosphere, thereby promoting the whisker growth rate.
[0010] This invention catalytically grows three-dimensional radial (sea urchin-like) SiC whiskers in situ on the surface of SiC microparticles, thus obtaining sea urchin-shaped SiC microparticles. This unique sharp / radial structure exhibits extremely high specific surface area and surface activity compared to traditional spherical or bulk SiC. In composite aerogels, the sea urchin-shaped SiC microparticles can more effectively penetrate and anchor within the SiO2 gel network, forming strong mechanical interlocking and interfacial bonding, significantly enhancing the interfacial strength of the composite material and preventing delamination and cracking.
[0011] 2) Pretreatment of sea urchin-shaped SiC particles: After washing the sea urchin-shaped SiC particles, they were mixed with NaOH solution and reacted. The solid reactants were collected by centrifugation, washed with water, and dried to obtain a surface rich in Si-O. - Urchin-like SiC microparticles with active sites.
[0012] The NaOH solution reacts with the amorphous SiO2 layer on the SiC surface (SiO2 + 2NaOH → Na2SiO3 + H2O), dissolving and removing part of the SiO2 layer, exposing the active silicon sites on the underlying SiC lattice surface. The exposed Si atoms then react with OH groups in the solution. - The combination forms silanol groups (Si-OH), which are then partially deprotonated to Si-O under weakly alkaline conditions. - This process imparts a negative charge to the particle surface, significantly increasing the absolute value of the Zeta potential. The resulting enhanced electrostatic repulsion effectively suppresses particle aggregation, enabling SiC microparticles to achieve a highly stable dispersion in the water-based dispersion system.
[0013] 3) Preparation of composite aerogel by in-situ polymerization: Sea urchin-shaped SiC microparticles are mixed with silicon source, anhydrous ethanol and water, and reacted under acidic conditions to obtain hydrolysate. The hydrolysate is transferred to a mold, and alkaline solution is added to adjust it to alkalinity. After drying and standing until gel-like, it is aged and dried to obtain sea urchin-shaped SiC-reinforced composite aerogel thermal insulation material (i.e., sea urchin-shaped SiC / SiO2 composite aerogel).
[0014] Sea urchin-like SiC microparticles, rich in Si-OH groups on their surface, undergo in-situ polymerization and complexation with SiO2 during gel formation, rather than simple mechanical mixing. The advantage lies in the dehydration condensation reaction between the Si-OH active sites on the SiC surface and the silica oligomers (containing a large amount of Si-OH groups) generated by the hydrolysis of the silicon source, forming a chemically bonded interface. This chemical bonding drives the preferential adsorption, deposition, and cross-linking polymerization of the silica oligomers on the SiC surface. As the condensation reaction proceeds, the SiC surface is gradually coated with a SiO2 gel layer, forming a "core-shell" or "coated" structure. Simultaneously, the three-dimensional protrusions of the sea urchin-like microparticles embed into the aerogel matrix, forming mechanical interlocking, which synergistically enhances the interfacial bonding force with the chemical bonding. This in-situ polymerization method significantly improves the interfacial compatibility between the inorganic filler and the aerogel matrix, effectively suppressing the volume shrinkage of the aerogel during drying and use, thereby improving the overall structural stability and mechanical properties of the material.
[0015] Furthermore, the introduction of sea urchin-shaped SiC microparticles into the SiO2 aerogel in this invention also provides a healing function: the sea urchin-shaped SiC microparticles not only serve as a reinforcing phase to improve the mechanical properties of the composite aerogel, but also play a unique functional role in high-temperature oxidizing environments. When the composite aerogel is used in a high-temperature oxygen-containing atmosphere, the surface of the sea urchin-shaped SiC microparticles undergoes an oxidation reaction, generating a dense SiO2 oxide layer. This newly formed SiO2 can effectively fill the microcracks, pore defects, and structural collapse areas generated in the aerogel skeleton at high temperatures, compensating for damage to the original aerogel network structure to a certain extent. This mechanism can significantly delay the performance degradation of the aerogel skeleton under high-temperature environments, improving the long-term structural stability and thermal insulation durability of the material under extreme conditions of 800°C and above.
[0016] Preferably, in step 1), the temperature of the vacuum sintering is 1350-1450℃.
[0017] In this invention, the vacuum sintering temperature has a decisive influence on whether sea urchin-shaped SiC microparticles can be formed. Within the aforementioned temperature range, which is the preferred range, the supersaturation of the gaseous precursor (SiO, CO, etc.) is suitable, SiC whiskers grow stably along a preferred orientation, with a uniform whisker diameter distribution of 100-200 nm, dense growth, and a radially uniform distribution on the surface of the SiC microparticles, resulting in a complete and dense sea urchin-like structure. When the temperature is too low (e.g., 1200℃), the reaction is insufficient, and the whisker growth density and length do not reach the ideal state; the sea urchin-like structure is basically formed, but some whiskers are not fully formed. When the temperature is too high (e.g., 1600℃), the reaction is too violent, the whisker growth rate becomes uncontrolled, leading to whisker coarsening, local melting and adhesion, blurred whisker edges, and partial destruction of the sea urchin-like structure. This invention obtains sea urchin-shaped SiC microparticles with a complete and dense sea urchin-like structure at a vacuum sintering temperature of 1400℃. Based on this, the present invention, combining the thermodynamic properties of the raw materials and the gas-liquid-solid (VLS) mechanism, reasonably derives that a complete and dense sea urchin-like structure can be obtained within the temperature range of 1350-1450℃. This derivation is based on the following: in the present invention, the eutectic temperature of the Si-C system is approximately 1400℃, the liquid phase window of the catalyst alloy covers 1300-1500℃, and 1350-1450℃ falls precisely within the core range of stable liquid phase existence; furthermore, the supersaturation of VLS growth changes continuously with temperature. According to conventional experience, a fluctuation of 50℃ will not cause a qualitative change in the growth behavior. Therefore, the preferred vacuum sintering temperature is derived to be 1350-1450℃.
[0018] More preferably, in step 1), the heating rate is 5-15℃ / min, and the holding time is 2-4h.
[0019] Preferably, in step 1), the diameter of the SiC whiskers is 100-200 nm.
[0020] Preferably, in step 1), the molar ratio of Si powder to C powder is 1:(0.8-1.2).
[0021] Preferably, in step 1), the thickness of the porous material is 0.5-1.5 cm.
[0022] Preferably, in step 1), the porous material is a porous carbon felt.
[0023] Preferably, in step 1), the method for preparing the SiC particles supported on the catalyst includes: immersing the SiC particles in a catalyst solution to carry out the reaction, and drying the reaction product.
[0024] The catalyst precursor ions in the catalyst solution are uniformly attached to the SiC surface. After drying, they are fixed on the surface of SiC particles, forming a uniform and stable catalyst support layer. This provides sufficient and uniformly distributed nucleation sites for subsequent VLS growth, thus ensuring the uniformity of the urchin-shaped SiC nanowire array.
[0025] More preferably, the particle size of the SiC microparticles is 1-5 micrometers.
[0026] More preferably, the catalyst in the catalyst solution is NiSO4; the catalyst content in the catalyst solution is (0.3-1g) / 100mL. The ratio of SiC particles to catalyst solution is 1g / (30-50)mL; the reaction temperature is room temperature, and the reaction time is 1-3h.
[0027] Preferably, in step 2), the concentration of the NaOH solution is 1.8-2.2 mol / L.
[0028] The concentration of NaOH solution has a certain influence on the modification effect of sea urchin-shaped SiC particles. Treatment with an appropriate concentration of NaOH solution can fully expose the active silicon sites on the surface of the sea urchin-shaped SiC particles, forming a high-density surface Si-O under weakly alkaline washing conditions (pH=8.5±0.5). - The negative charge layer maximizes the absolute value of the Zeta potential, resulting in the lowest viscosity and optimal dispersibility in alkaline aqueous dispersion systems. When the NaOH concentration is low (e.g., 1.0 mol / L), the SiO2 layer is not fully dissolved, the active sites are insufficiently exposed, the surface negative charge density is low, and both dispersibility and reactivity are not ideal. When the NaOH concentration is high (e.g., 3.0 mol / L), excessive etching can damage the urchin-like surface spikes, thus reducing dispersibility. Furthermore, excessively high alkali concentrations increase reagent consumption and post-processing costs. This invention obtained well-dispersed urchin-like SiC particles in a 2.0 mol / L NaOH solution. Based on this, it is reasonable to deduce that similar technical effects can be obtained in a concentration range of 1.8-2.2 mol / L. This deduction is based on the fact that the reaction rate of alkaline etching of the SiO2 layer is related to the OH concentration. - The concentrations exhibit a continuous linear relationship, with 2.0 mol / L and 2.2 mol / L varying by only ±10% relative to 2.0 mol / L, respectively, all fluctuating at the same concentration level. Therefore, both empirically and theoretically, the etching degree within the range of 1.8–2.2 mol / L is close to the optimal state of 2.0 mol / L, falling within a moderate etching range, and good dispersibility can be achieved within this concentration range.
[0029] More preferably, in step 2), the ratio of the amount of sea urchin-shaped SiC particles to NaOH solution is 1 g / (40-60) mL.
[0030] Preferably, in step 2), the reaction temperature is 70-90℃ and the time is 1-3h.
[0031] Preferably, in step 2), the cleaning of the sea urchin-shaped SiC particles includes: first cleaning the sea urchin-shaped SiC particles with anhydrous ethanol, and then washing them with water.
[0032] Preferably, in step 2), the drying is vacuum drying, with the following conditions: temperature 50-60℃, vacuum degree <-0.08MPa, and time 8-20h.
[0033] Preferably, in step 3), the urchin-shaped SiC particles account for 1-5 wt% (more preferably 1-4.5 wt%) of the theoretical mass of SiO2 in the silicon source.
[0034] Sea urchin-shaped SiC microparticles have a suitable addition range. At a suitable addition amount (e.g., around 4 wt%), the radial structure of the sea urchin-shaped SiC microparticles can form a uniform three-dimensional reinforcing network in the aerogel, achieving good mechanical interlocking and chemical bonding with the SiO2 matrix. At the same time, SiC is oxidized at high temperature to form a dense SiO2 layer, which can repair the framework to a certain extent, and the mechanical properties and high-temperature structural stability are both optimal. When the addition amount is too high (e.g., 5 wt%), the sea urchin-shaped SiC microparticles locally agglomerate in the matrix, leading to stress concentration and increased density, decreased compressive strength and specific surface area retention, a grainy surface, and a decline in overall performance.
[0035] Preferably, in step 3), the molar ratio of the silicon source, anhydrous ethanol and water is 1:(3-5):(3-5).
[0036] More preferably, in step 3), the silicon source is tetraethyl orthosilicate.
[0037] Preferably, in step 3), the pH of the reaction is 3-4, the temperature is 25-60℃, and the time is 30min-2h.
[0038] Preferably, in step 3), the alkaline pH is 7.5-9.5.
[0039] Preferably, in step 3), the aging process involves adding anhydrous ethanol for aging replacement for 40-60 hours.
[0040] Preferably, in step 3), the drying is supercritical drying using anhydrous ethanol as the medium.
[0041] Compared with the prior art, the beneficial effects of the present invention are: (1) Significantly improved interfacial bonding strength: During the process of silicon source hydrolysis to form SiO2, on the one hand, the three-dimensional radial structure of sea urchin-like SiC particles forms a mechanical interlock with the SiO2 network; on the other hand, the surface Si-O introduced by alkali treatment... - The active sites undergo a dehydration condensation reaction with the Si-OH of the silica oligomer to form a strong chemical bond interface. The combined physical and chemical action significantly improves the interfacial bonding strength compared to traditional mechanical mixing methods, effectively preventing the delamination and cracking of the composite aerogel.
[0042] (2) Significantly improved structural stability and mechanical properties: The active sites on the surface of the sea urchin-like SiC microparticles serve as preferential deposition anchors for silica oligomers, guiding preferential cross-linking and coating of SiO2 to form a core-shell coated structure, which can effectively suppress the volume shrinkage of the composite aerogel during drying and use. The mechanical properties (compressive strength and flexural strength) of the composite aerogel are significantly improved compared with pure SiO2 aerogel, while maintaining the structural characteristics of high porosity and low density.
[0043] (3) High-temperature oxidation enables in-situ repair and long-term protection: In a high-temperature oxygen-containing environment, urchin-shaped SiC particles will oxidize to form a dense SiO2 layer, which can automatically fill the microcracks and pore defects generated by the aerogel skeleton and repair structural damage. After high-temperature oxidation treatment, the pore structure of the composite aerogel remains intact, and there is no obvious skeleton collapse.
[0044] (4) Efficient and controllable process: The present invention can achieve integrated molding by using an in-situ polymerization strategy combined with the coordinated control of process parameters. The process is simplified, the operation is convenient and the repeatability is good. It avoids the problems of easy agglomeration and uneven dispersion of the reinforcing phase, and is suitable for large-scale production. Attached Figure Description
[0045] Figure 1 SEM (5 μm) of the sea urchin-shaped SiC microparticles prepared in Examples 1-2 of this invention. Figure 2 SEM (1 μm) of the sea urchin-shaped SiC microparticles prepared in Examples 1-1 (left), 1-2 (middle), and 1-3 (right) of this invention. Figure 3 EDS of the sea urchin-shaped SiC microparticles prepared in Examples 1-2 of this invention; Figure 4 XRD patterns of the sea urchin-shaped SiC microparticles prepared in Examples 1-2 of this invention.
[0046] Figure 5 This is a photograph of the product prepared in Comparative Example 1 of the present invention. Detailed Implementation
[0047] The present invention will be further described below with reference to embodiments.
[0048] Example 1: Effect of different sintering temperatures on the structure of sea urchin-like SiC microparticles (1) Dissolve 0.5g of catalyst NiSO4 in 100mL of deionized water and stir at room temperature for 30min to obtain a mixed solution.
[0049] (2) Soak 2g of SiC particles (with a particle size of about 3μm) in the above mixed solution for 2h, and then dry them in a drying oven at 105℃ for 2h to obtain SiC particles with catalyst supported.
[0050] (3) The porous carbon felt was ultrasonically cleaned with deionized water and anhydrous ethanol respectively, and after being impregnated with a mixture of 5g phenolic resin and 55mL anhydrous ethanol, it was placed in a drying oven and dried at 100℃ for 4 hours to obtain a porous carbon felt pre-impregnated with phenolic resin.
[0051] (4) Weigh out Si powder and C powder in equal molar ratio and mix them evenly (2g of mixed powder). Spread the mixed powder evenly on the bottom layer (2mm thickness) of a graphite crucible (5cm inner diameter). Then, spread the porous carbon felt (1cm thickness) pre-impregnated with phenolic resin and the SiC particles loaded with catalyst (2mm thickness) on top. Cover the graphite crucible with a lid and place the whole thing in a vacuum tube high-temperature sintering furnace.
[0052] (5) Increase the temperature to the set temperature at 10℃ / min (see Table 1 for specific temperatures) and keep warm for 2 hours.
[0053] (6) Then cool down at 10℃ / min until room temperature is reached.
[0054] (7) Finally, SiC whiskers are grown on the surface of SiC particles to form a sea urchin structure. After washing with water, the porous carbon felt is carefully peeled off to obtain sea urchin-shaped SiC particles. The whisker diameter and growth density are shown in Table 1.
[0055] Table 1
[0056] The data comparison in Table 1 shows that Examples 1-2 (sintering temperature 1400℃) represent the optimal process conditions. Under these conditions, the supersaturation of the gaseous precursors (SiO, CO, etc.) is suitable, and the SiC whiskers grow stably along their preferred orientation, with a uniform whisker diameter distribution of 100-150 nm (e.g., ...). Figure 2 As shown in the middle figure), the growth density is dense, and it is evenly distributed radially on the surface of SiC particles, with a complete and dense sea urchin-like structure. Figure 1 When the temperature is too low (1200℃, as in Example 1-1), the reaction is still insufficient, some whiskers do not form completely, and the whisker growth density and length do not reach the ideal state (e.g. Figure 2As shown in the left figure); when the temperature is too high (1600℃, as in Examples 1-3), the reaction becomes too violent, the whisker growth rate becomes uncontrolled, resulting in whisker coarsening (150-220nm), and local fusion and adhesion occur, blurring the whisker edges (as shown in the left figure). Figure 2 As shown in the right figure, the urchin-like structure is partially destroyed.
[0057] Figure 3 EDS of the sea urchin-shaped SiC microparticles prepared in Examples 1-2 of this invention; Figure 4 XRD patterns of the sea urchin-shaped SiC microparticles prepared in Examples 1-2 of this invention.
[0058] Comparative Example 1 The only difference between Comparative Example 1 and Examples 1-2 is that a porous carbon felt was not laid before the vacuum sintering process. The specific steps are as follows: (1) Dissolve 0.5g of catalyst NiSO4 in 100mL of deionized water and stir at room temperature for 30min to obtain a mixed solution.
[0059] (2) Soak 2g of SiC particles (with a particle size of about 3μm) in the above mixed solution for 2h, and then dry them in a drying oven at 105℃ for 2h to obtain SiC particles with catalyst supported.
[0060] (3) Weigh out Si powder and C powder in equal molar ratio and mix them evenly (2g of mixed powder). Spread the mixed powder evenly on the bottom layer of the graphite crucible (5cm inner diameter) (2mm thickness). Spread the SiC particles loaded with catalyst (2mm) on top, cover the graphite crucible with the lid, and place the whole thing in a vacuum tube high-temperature sintering furnace.
[0061] (4) Increase the temperature to 1400℃ at 10℃ / min and keep it warm for 2 hours.
[0062] (5) Then cool down at 10℃ / min until room temperature is reached.
[0063] (6) For example Figure 5 As shown, because SiC particles are in direct contact with Si powder and C powder at high temperature, the particles are sintered at high temperature, and the final product is an agglomeration into a blocky ceramic sintered body with no obvious sea urchin-like nanowire structure on the surface, and it is impossible to obtain a dispersed powder product.
[0064] Example 2: Effect of different concentrations of NaOH solution on surface pretreatment of sea urchin-shaped SiC microparticles (1) Place 1g of sea urchin-shaped SiC particles (Examples 1-2) and 50mL of anhydrous ethanol in a 100mL beaker, sonicate for 10min, centrifuge at 8000rpm for 5min, discard the supernatant, and repeat twice.
[0065] (2) Replace anhydrous ethanol with deionized water and repeat the above ultrasonic-centrifugation operation twice to wash away residual ethanol.
[0066] (3) Transfer the cleaned sea urchin-shaped SiC particles to a 250mL three-necked flask, add 50mL of NaOH aqueous solution of different concentrations (see Table 2 for specific concentrations), and stir magnetically in an 80℃ constant temperature water bath for 2h. After the reaction, let it cool naturally to room temperature.
[0067] (4) Centrifuge the reaction solution at 8000 rpm for 5 min and discard the supernatant.
[0068] (5) Add 50 mL of deionized water, stir for 2 min and centrifuge (8000 rpm, 5 min), discard the supernatant. Repeat the operation until the pH of the supernatant is 8.5 ± 0.5 and the conductivity is < 10 μS / cm.
[0069] (6) The obtained sea urchin-shaped SiC particles were transferred to a vacuum drying dish and dried at 60°C and a vacuum degree of <-0.08MPa for 12 hours.
[0070] (7) After drying, the sea urchin-shaped SiC particles were removed, sealed, and stored in a desiccator for later use. The modification effect is shown in Table 2.
[0071] Table 2
[0072] Note: (a) The Zeta potential of SiC particles in each dispersion was measured using a Zeta potential analyzer. Each sample was measured in triplicate, and the average value ± standard deviation was taken. (b) Dispersibility in an aqueous system was determined by viscosity testing (the modified SiC particles were dispersed in deionized water with the same solid content, the pH was adjusted to 10, and the viscosity of the slurry was measured using a rotational viscometer. The lower the viscosity, the lower the degree of agglomeration between particles and the better the dispersibility).
[0073] The data comparison in Table 2 shows that Example 2-2 (NaOH concentration 2.0 mol / L) represents the optimal process conditions. After treatment with a 2 mol / L NaOH solution, the zeta potential of the sea urchin-like SiC particles was the highest, and the viscosity was the lowest in the aqueous dispersion system at pH=10, indicating the best dispersibility. At a NaOH concentration of 1.0 mol / L (Example 2-1), the SiC surface etching was insufficient, and the dispersibility did not reach the ideal state. When the NaOH concentration was increased to 3.0 mol / L (Example 2-3), excessive surface etching occurred, which weakened the dispersion stability. Therefore, 2.0 mol / L is the optimal concentration.
[0074] Example 3: Effect of the amount of sea urchin-shaped SiC microparticles added on the properties of composite aerogel (1) According to the molar ratio of n(tetraethyl orthosilicate):n(anhydrous ethanol):n(H2O)=1:4:4, add tetraethyl orthosilicate, anhydrous ethanol and deionized water into a beaker, stir magnetically for 5 min to mix the system evenly, add sea urchin-shaped SiC particles (Example 2-2, the specific amount added is shown in Table 3, calculated based on the theoretical mass of SiO2 in the silicon source by the sea urchin-shaped SiC particles), stir magnetically for 10 min to initially disperse them in the reaction system.
[0075] (2) Place the mixture obtained in (1) in a constant temperature water bath at 25℃, slowly add 0.1mol / L HNO3 solution to adjust the pH to 3.8, stir the mixture in the constant temperature water bath for 30min to obtain the hydrolysate.
[0076] (3) Transfer the hydrolysate to the mold, add 1 mol / L ammonia to adjust the pH to 8, and let it stand at room temperature until gel forms.
[0077] (4) After the gel forms, anhydrous ethanol is added for aging and replacement for 48 hours. Then, supercritical drying is performed using anhydrous ethanol as the medium to obtain sea urchin-like SiC / SiO2 composite aerogel. The properties are shown in Table 3.
[0078] Table 3
[0079] Note: Compressive strength was tested using a universal electronic testing machine for uniaxial compression. Aerogel samples were processed into regular cubes (20mm × 20mm × 20mm) and compressed at a constant loading rate of 10mm / min. The stress-strain curves were recorded, and the compressive stress value corresponding to 20% strain was read. Specific surface area retention was determined using the BET method after heat treatment at 1000℃ for 0.5h. Before testing, samples were vacuum degassed at 150℃ to remove adsorbed impurities, and then tested using a specific surface area and pore size analyzer. The specific surface area was calculated using the BET equation based on the N2 adsorption isotherm.
[0080] As shown in Table 3, the optimal addition amount of sea urchin-shaped SiC microparticles is 4wt% (Example 3-3). At this point, the compressive strength of the composite aerogel under 20% compressive strain reaches 1.2MPa, which is more than 100% higher than that of the traditional SiO2 aerogel (Example 3-1, 0wt%). After heat treatment at 1000℃ for 0.5h, the specific surface area retention rate is higher than 55%, and the macroscopic morphology is intact without cracks. Pure SiO2 aerogel lacks a reinforcing phase, resulting in poor mechanical properties and severe collapse of the high-temperature skeleton, with a specific surface area retention rate of only 22.1%. When the addition amount is increased to 3 wt% (Example 3-2), the reinforcing effect initially appears, with improvements in both compressive strength and specific surface area retention rate, but these are not yet optimal. When the addition amount is further increased to 4 wt% (Example 3-3), the radial structure of the sea urchin-like SiC particles forms a uniform three-dimensional reinforcing network in the aerogel, achieving good mechanical interlocking and chemical bonding with the SiO2 matrix. At the same time, SiC oxidizes at high temperatures to generate a dense SiO2 layer, which heals and repairs the skeleton, resulting in optimal mechanical properties and high-temperature structural stability. However, when the addition amount continues to increase to 5 wt% (Example 3-4), the sea urchin-like SiC particles locally agglomerate in the matrix, leading to stress concentration and increased density. This results in a decrease in both compressive strength and specific surface area retention rate, a grainy texture on the surface, and a decline in overall performance.
[0081] Unless otherwise specified, the raw materials and equipment used in this invention are all commonly used in the field; unless otherwise specified, the methods used in this invention are all conventional methods in the field.
[0082] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, alterations, and equivalent transformations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A method for preparing a sea urchin-shaped SiC-reinforced composite aerogel insulation material, characterized in that: Includes the following steps: 1) Preparation of sea urchin-shaped SiC microparticles: Si powder and C powder are mixed and spread evenly on the bottom of the sintering container, and then porous material pre-impregnated with phenolic resin and SiC microparticles loaded with catalyst are laid in sequence. The temperature is raised to 1350-1450℃ and then vacuum sintered. The porous material is washed with water to remove it, and SiC microparticles with SiC whiskers grown on the surface are obtained, i.e., sea urchin-shaped SiC microparticles. 2) Pretreatment of sea urchin-shaped SiC particles: After washing the sea urchin-shaped SiC particles, they were mixed with a 1.8-2.2 mol / L NaOH solution for reaction. The solid reactants were collected by centrifugation, washed with water, and dried to obtain a surface rich in Si-O. - Urchin-like SiC particles with active sites; 3) Preparation of composite aerogel by in-situ polymerization: Sea urchin-shaped SiC microparticles are mixed with silicon source, anhydrous ethanol and water, and reacted under acidic conditions to obtain hydrolysate. The hydrolysate is transferred to a mold, adjusted to alkaline, dried and allowed to stand until gel-like, aged and dried to obtain sea urchin-shaped SiC reinforced composite aerogel thermal insulation material.
2. The preparation method according to claim 1, characterized in that: In step 1), the diameter of the SiC whiskers is 100-200 nm.
3. The preparation method according to claim 1 or 2, characterized in that: In step 1): The molar ratio of Si powder to C powder is 1:(0.8-1.2). The thickness of the porous material is 0.5-1.5 cm; The porous material is a porous carbon felt; The heating rate is 5-15℃ / min, and the holding time is 2-4h.
4. The preparation method according to claim 1 or 2, characterized in that: In step 1), the method for preparing the SiC particles supported on the catalyst includes: immersing the SiC particles in a catalyst solution to carry out the reaction, and drying the reaction product.
5. The preparation method according to claim 4, characterized in that: In step 1): The particle size of the SiC microparticles is 1-5 micrometers; The catalyst in the catalyst solution is NiSO4; The catalyst content in the catalyst solution is (0.3-1g) / 100mL; The ratio of SiC microparticles to catalyst solution is 1 g / (30-50) mL; The reaction was carried out at room temperature for 1-3 hours.
6. The preparation method according to claim 1, characterized in that: In step 2): The ratio of the sea urchin-shaped SiC particles to the NaOH solution is 1 g / (40-60) mL; The reaction is carried out at a temperature of 70-90℃ for 1-3 hours.
7. The preparation method according to claim 1 or 6, characterized in that: In step 2): The cleaning process for the sea urchin-shaped SiC particles includes: first cleaning the sea urchin-shaped SiC particles with anhydrous ethanol, and then washing them with water. The drying process is vacuum drying, with the following conditions: temperature 50-60℃, vacuum degree <-0.08MPa, and time 8-20h.
8. The preparation method according to claim 1, characterized in that: In step 3): the urchin-shaped SiC particles account for 1-5 wt% of the theoretical mass of SiO2 in the silicon source.
9. The preparation method according to claim 1 or 8, characterized in that: In step 3): The molar ratio of the silicon source, anhydrous ethanol, and water is 1:(3-5):(3-5); The reaction is carried out at a pH of 3-4, a temperature of 25-60℃, and a time of 30 min-2 h. The alkaline pH is 7.5-9.
5.
10. The preparation method according to claim 1 or 8, characterized in that: In step 3): The aging process involves adding anhydrous ethanol for aging and replacement for 40-60 hours. The drying process is supercritical drying using anhydrous ethanol as the medium.